CALCULATION OF ANNUAL PREMIUM RESERVES FOR INDIVIDUAL HEALTH INSURANCE USING THE PROSPECTIVE METHOD - Rido Evendi Tarigan; Putri Yolana Pardede; Tesalonika Manik (Parameter: Journal of Statistics, 2026)
Premium reserve management is an important aspect of health insurance because inaccurate reserve calculations may affect an insurer's ability to meet future claim obligations. This study aims to calculate and compare annual premium reserves for individual health insurance under two types of insurance products, namely term insurance and whole life insurance, using the Prospective Method. The analysis was conducted through a simulation involving a family of three consisting of a father aged 40 years, a mother aged 36 years, and a son aged 9 years. The calculations were based on the CSO 1941 mortality table, an annual interest rate of 2.5%, and health insurance benefits covering Rp 200.000 per day for hospital room charges, Rp 75.000 per day for physician visits with a maximum of 180 days, and Rp 4.000.000 per treatment period for medical expenses. The results indicate that the annually renewable premium increases with the insured's age, with the total premium rising from Rp 704.060 in the first year to Rp 1.196.260 in the tenth year. The reserve values obtained using the Prospective Method show different patterns for the two insurance products. Premium reserves for term insurance gradually decrease over the policy period and reach zero at the end of the contract, whereas premium reserves for whole life insurance increase continuously from year to year. These findings demonstrate the different reserve characteristics of term and whole life insurance and provide useful actuarial information for insurers in planning and managing long-term reserve funds.